2000
DOI: 10.1046/j.1365-2265.2000.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of missense mutations in the SRD5A2 gene from patients with steroid 5α‐reductase 2 deficiency

Abstract: Four different single base mutations that cause amino acid substitutions were detected in the steroid 5alpha-reductase type 2 gene of affected individuals. One patient and a normal control had two previously undescribed mutations. Although in the latter individual we cannot exclude the possibility that the base change is a genetic polymorphism, the molecular screening of 100 chromosomes suggests strongly that the change at codon 245 does represent a heterozygous mutation. Further studies, including the recreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…Nearly 40% of the subjects we studied were homozygous or heterozygous for Pro212 ? Arg Vilchis et al 2000;Chávez et al 2000). The prevalence of alterations at this site in Mexican patients could be the result of a founder gene effect.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 40% of the subjects we studied were homozygous or heterozygous for Pro212 ? Arg Vilchis et al 2000;Chávez et al 2000). The prevalence of alterations at this site in Mexican patients could be the result of a founder gene effect.…”
Section: Discussionmentioning
confidence: 99%
“…Single-stranded conformational polymorphism (SSCP) analysis of PCR products was performed according to the method of Orita (1989), using [α-32 P] deoxycytidine triphosphate as described elsewhere (Vilchis et al 2000). Sequencing of the mutant and normal PCR fragments was carried out with the Thermosequenase ([α-33 P] dideoxynucleotide triphosphate) terminator cycle sequencing kit (Amersham, Cleveland, OH, USA), following the manufacturer's recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…However, in many instances, this method has failed as a good predictor and various other approaches have been proposed [22,39,41,45,49], urinary steroid profiling (UPS) and gene mutation analysis being two alternatives. Chan et al suggested that UPS results can be misinterpreted; thus, molecular [25,39,40] p.G115D/p.G115D 5 2.60 0.55 [22,39,41,42] analysis was considered the most effective diagnostic method also taking into account the small size of the gene makes the diagnostic procedure easier [50].…”
Section: Diagnosismentioning
confidence: 99%